Analysis of customer intention to save at BMT Fastabiq Jepara - Sudarsono, Heri; Alghana, Ahada Dzulfikar; Ash Shidiqie3, Jannahar Saddam; El Hasanah, Lak lak Nazhat (ITB AAS INDONESIA Surakarta, 2024)
This research aims to analyze the intention to save at BMT Fastabiq, Jepara. This research was conducted from May to June 2023, and the data source was obtained through a survey method using a questionnaire tool that was distributed to customers at BMT Fastabiq Jepara. This research uses quantitative data processing methods with SEM PLS analysis (Partial Least Square ) using SmartPLS 4.0. The respondents in this study were 100 BMT Fastabiq Jepara customers. The variables used in this research were intention to save (INT), knowledge (KNW), products (PRD), promotions (PRM), and religiosity (RE). The results of this research reveal that products and religiosity have a positive effect on the intention to save at BMT Fastabiq Jepara, whereas knowledge and promotion do not affect customers' intention to save at BMT Fastabiq Jepara.